Seven years of experimental warming and nutrient addition causes decline of bryophytes and lichens in alpine meadow and heath communities - Alatalo,Juha M; Jägerbrand,Annika K; Molau,Ulf (PeerJ PrePrints, 2014)
Global change is predicted to have large and rapid impact on polar and alpine regions. Bryophytes and lichens increase their importance in terms of biomass, carbon/nutrient cycling, cover and ecosystem functioning at higher latitudes/altitudes. Here we report from a seven year factorial experiment with nutrient addition and warming on the abundance of bryophytes and lichens in an alpine meadow and heath community. Treatments had significant negative effect on relative change of total abundance bryophytes and lichens, the largest decline to the nutrient addition and the combined nutrient addition and warming treatments, bryophytes decreasing most in the meadow, lichens most in the heath. Nutrient addition, and the combined nutrient addition and warming brought rapid decrease in both bryophytes and lichens, while warming had a delayed negative impact. Of sixteen species that were included the statistical analyses, we found significant negative effects on seven species. We show that impact of simulated global change on bryophytes and lichens differ in in time and magnitude among treatments and plant communities. Our results underscore the importance of longer-term studies to improve the quality of climate change models, as short-term studies are poor predictors of longer-term responses of bryophytes and lichens, similar to what have been shown for vascular plants. Species-specific responses may differ in time, and this will likely cause changes in the dominance structures of bryophytes and lichens over time.
Keywords: climate change; Arctic; cryptogams; meadow; mosses; global change; environmental change; heath; dominant species; tundra